Cyberfeminism: The Opportunity and Challenges Of Social Media For Indonesian Women Empowerment - Suharnanik Suharnanik (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
Social media is a communication medium that connected to the internet, as a communication medium that is connected online and has global access. Cyberfeminism is an ideology that uses new media as well as social media and a vehicle to empower and liberate women independently from the domination of male discourse. The aims of this research is to analyze the opportunities and challenges of social media for the empowerment of Indonesian women. This research method is a literature review and secondary data analysis based on women's empowerment index data with the percentage of Indonesia's population accessing the internet based on gender. The theory in this study is cyberfeminism to voice women to optimize their mastery of new media technology as an effort to empower them. This research produces an analysis that women still have enormous opportunities in utilizing social media to obtain information, a more inclusive social life, and increase economic and political empowerment for women. Although the challenge of overcoming problems related to the negative effects of social media must be overcome.